2012
DOI: 10.1093/geronb/gbs064
|View full text |Cite
|
Sign up to set email alerts
|

Friend or Foe? Age Moderates Time-Course Specific Responsiveness to Trustworthiness Cues

Abstract: This study provided initial evidence that the age-related positivity effect in affective processing extends to subtle emotional cues, generally interpreted as being reflective of socially relevant personality traits. Implications for aging theories of motivated cognition and developmental changes in reliance on superficial affective cues are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
41
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(52 citation statements)
references
References 37 publications
7
41
4
Order By: Relevance
“…This lack of an interaction is consistent with the trust decay model in which a dual process ensures that the most reliable information takes precedence (see Chang et al, 2010). Because of reduced cognitive capacity for decision-making with age (see Peters et al, 2011), these dual processes were not expected to merge for older adults, and no interaction between facial appearance and thirdparty reputational information was expected.…”
supporting
confidence: 74%
See 3 more Smart Citations
“…This lack of an interaction is consistent with the trust decay model in which a dual process ensures that the most reliable information takes precedence (see Chang et al, 2010). Because of reduced cognitive capacity for decision-making with age (see Peters et al, 2011), these dual processes were not expected to merge for older adults, and no interaction between facial appearance and thirdparty reputational information was expected.…”
supporting
confidence: 74%
“…Although an age-related decrease in attention to superficial facial cues to trustworthiness has been documented (Castle et al, 2012), other research has found no age difference in ratings of trustworthiness in computer-generated faces (Petrican et al, 2012). However, it was also shown that older (but not younger) adults were more likely to follow the eye gaze of trustworthy-than untrustworthy-looking faces (Petrican et al, 2012).…”
mentioning
confidence: 93%
See 2 more Smart Citations
“…It should be noted, that this was not the first study examining a potential influence of trustworthiness on gaze cueing, however these studies yielded inconsistent results. Although some studies -implicitly (Bayliss & Tipper, 2006) or explicitly (King et al, 2011) investigating the effects of trustworthiness on gaze cueingcould not find any moderating effect, other studies found effects of trustworthiness (e.g., Petrican et al, 2013) at least in specific populations. Particular strengths of our study might account for the different results compared to King et al (2011) and Bayliss and Tipper (2006).…”
Section: Influence Of Trust On Gaze Cueingmentioning
confidence: 96%